Effectiveness of Garcinia mangostana Mangosteen Peel Extract in Inhibiting Gram-Negative Bacteria in Lobster (Panulirus homarus) Aquaculture Waters - Muahiddah, Nuri; Alim, Sahrul; Mulyani, Laily Fitriani (Journal of Fish Health, 2024)
This study aims to examine the effectiveness of mangosteen peel extract (Garcinia mangostana) in inhibiting the growth of Gram-negative bacteria in lobster (Panulirus homarus) aquaculture waters. The main problem in lobster farming is bacterial infections that can cause disease and mass mortality. Mangosteen peel extract is known to contain potent antimicrobial compounds. This research employs an experimental method with various concentrations of mangosteen peel extract to test its effect on the growth of Gram-negative bacteria. Based on result, the mangosteen peel inhibition zone against Gram-negative bacteria from lobster aquaculture waters measures 0.25Â±0.05 cm (25 mm), indicating weak inhibition activity. This suggests that mangosteen peel could be used as an immunostimulant alternative to antibiotics in combating diseases in lobsters. Further research is needed to determine the optimal dosage of mangosteen peel extract to achieve strong inhibition activity against bacteria.